COASTAL HEROINE: HALAL KNOWLEDGE TRANSFORMATION OF WOMEN ENTREPRENEURS IN THE EAST COAST OF SUMATRA - Mubyarto, Novi; Martaliah , Nurfitri; Ramli , Fauzan; Saadah, Mar Atun; Safitri , Yuliana (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
Study aims to analyze the transformation of halal product assurance knowledge from training and implementation of halal assurance systems in the coastal areas of Sumatra. Processed seafood products in Tungkal Ilir Subdistrict, Tanjung Jabung Timur Regency have not been able to access a wide market share due to the lack of halal assurance knowledge which has an impact on the absence of Halal Certificates. By applying qualitative methods, researchers conducted participatory observations and focused discussions with female entrepreneurs. The results of this study indicate that the transformation of knowledge about halal product assurance changes at least five aspects in the production of processed seafood in this area. There is an increase in knowledge about the urgency of halal certification, halal sharia provisions and knowledge about the halal certification process. Halal knowledge which was originally limited to raw materials has increased to an understanding of the criteria for auxiliary materials, production processes, product naming to the monitoring and evaluation process of halal assurance implementation. In addition, there is also a change in behavior that was originally unable to process halal certification, to being able to access the halal page and fill in SJPH files online.